Chamomile decoction extract inhibits human neutrophils ROS production and attenuates alcohol-induced haematological parameters changes and erythrocytes oxidative stress in rat. Issue 1 (December 2016) - Jabri, Mohamed-Amine; Sani, Mamane; Rtibi, Kais; Marzouki, Lamjed; El-Benna, Jamel; Sakly, Mohsen; Sebai, Hichem
Abstract Background The aim of this study was to evaluate the protective effects of subacute pre-treatment with chamomile (Matricaria recutita L.) decoction extract (CDE) against stimulated neutrophils ROS production as well as ethanol (EtOH)-induced haematological changes and erythrocytes oxidative stress in rat. Methods Neutrophils were isolated and ROS generation was measured by luminol-amplified chemiluminescence. Superoxide anion generation was detected by the cytochrome c reduction assay. Adult male wistar rats were used and divided into six groups of ten each: control, EtOH, EtOH + various doses of CDE (25, 50, and 100 mg/kg, b.w. ), and EtOH+ ascorbic acid (AA). Animals were pre-treated with CDE extract during 10 days. Results We found that CDE inhibited (P ≤ 0.0003) luminol-amplified chemiluminescence of resting neutrophils and N-formyl methionylleucyl-phenylalanine (fMLF) or phorbolmyristate acetate (PMA) stimulated neutrophils, in a dose-dependent manner. CDE had no effect on superoxide anion, but it inhibited (P ≤ 0.0004) H2 O2 production in cell free system. In vivo, CDE counteracted (P ≤ 0.0034) the effect of single EtOH administration which induced (P < 0.0001) an increase of white blood cells (WBC) and platelets (PLT) counts. Our results also demonstrated that alcohol administration significantly (P < 0.0001) induced erythrocytes lipoperoxidation increase and depletion of sulfhydryl groups (−SH) content as well as antioxidant enzyme activities as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). More importantly, we found that acute alcohol administration increased (P < 0.0001) erythrocytes and plasma hydrogen peroxide (H2 O2 ), free iron, and calcium levels while the CDE pre-treatment reversed increased (P ≤ 0.0051) all these intracellular disturbances. Conclusions These findings suggest that CDE inhibits neutrophil ROS production and protects against EtOH-induced haematologiacal parameters changes and erythrocytes oxidative stress. The haematoprotection offered by chamomile might involve in part its antioxidant properties as well as its opposite effect on some intracellular mediators such as H2 O2, free iron, and calcium.